2008
DOI: 10.1017/s0007114507862398
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid iodine concentrations do not vary in pregnant women with varying iodine intake

Abstract: Iodine deficiency is an important clinical and public health problem. Its prevention begins with an adequate intake of iodine during pregnancy. International agencies recommend at least 200 mg iodine per d for pregnant women. We assessed whether iodine concentrations in the amniotic fluid of healthy pregnant women are independent of iodine intake. This cross-sectional, non-interventional study included 365 consecutive women who underwent amniocentesis to determine the fetal karyotype. The amniocentesis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
(15 reference statements)
0
14
0
1
Order By: Relevance
“…In this regard, we have found that KI supplements are as effective as multivitamins to reach adequate UIC. However, for BMIC, the differences among the 3 groups are not significant, probably due to 2 different facts: (a) the transport of iodine against a high-concentration gradient performed by the Na(+)/I(-) symporter tends to achieve higher BMIC even in women who had very low UIC, and (b) the effectiveness of multivitamins to increase BMIC might not be as effective as KI supplements, similar to what happens in amniotic fluid [15] . In our previous study in lactating women [11] , iodine in breast milk was negatively associated with different oxidative stress markers and with adiponectin levels.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, we have found that KI supplements are as effective as multivitamins to reach adequate UIC. However, for BMIC, the differences among the 3 groups are not significant, probably due to 2 different facts: (a) the transport of iodine against a high-concentration gradient performed by the Na(+)/I(-) symporter tends to achieve higher BMIC even in women who had very low UIC, and (b) the effectiveness of multivitamins to increase BMIC might not be as effective as KI supplements, similar to what happens in amniotic fluid [15] . In our previous study in lactating women [11] , iodine in breast milk was negatively associated with different oxidative stress markers and with adiponectin levels.…”
Section: Discussionmentioning
confidence: 94%
“…Pregnant women had higher median levels and lower prevalence of low levels than nonpregnant women. These findings can reflect a difference in renal clearance or dietary intake of iodine among these women (21,22). Further work is necessary to better define the causes of these differences and to achieve prevalence data that are representative of pregnant women in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Those women who had taken multivitamin supplements, however, showed no change in their UICs, even though many of these preparations contain variable amounts of iodine. Garcia-Fuentes et al [43] claims that, in order to achieve the objective of an adequate iodine intake during pregnancy, an active prescription of an iodine preparation that can be administered independently is preferable [43]. Magnesium plays an important role in numerous biochemical processes, which could have a protective effect on the developing fetus' brain [13].…”
Section: Discussionmentioning
confidence: 99%